Analysis of nosologies in the students of special medical group in connection with the application of contemporary means of therapeutic physical culture - Бісмак / Bismak E., Олена Василівна; Пешкова / Peshkova O., Ольга Володимирівна (Slobozhanskyi Herald of Science and Sport, 2012)
In the article, the results of the analysis of diseases in students of Kharkiv National University by V. N. Karasin are presents; the modern methods of remedial physical culture for the students of special medical groups in various diseases are characterized. The problems of complement of medical groups, organizing and conducting of physical culture with the students of the medical special group are actual and require further study